Ukraine: Russian court upholds 13-year sentence against Ukrainian human rights defender Maksym Butkevych - Amnesty International (Amnesty International, 2023)
An appeal hearing at a Moscow court on Tuesday (22 August) which has upheld the 13-year sentence imposed on Maksym Butkevych, a Ukrainian human rights defender, is a grave miscarriage of justice Amnesty International said today.
Ukraine
Keywords: 2023-08 August; Russia